Teologi Posmodern: Menimbang Konsep Naturalisme-Teistik - Ghozi, Ghozi (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2012)
This article will briefly discuss the problems of postmodern theology in the context of the relationship between God and nature. In this case, the author brings the conception of theistic naturalism in the view of classical theology of Islam. Theological conception of postmodernism (theistic naturalism) can be useful contributions to the refreshment of Islamic theology, particularly in the case af?âl al-?ibâd and its derivation. The concept of direct influence and indirect influence may help explain the intervention of God toward human beings without denying the law of causality, as the law that becomes standard of modern science. Nevertheless there are some things that need to be considered in this concept: Firstly, God is only the spirit of the universe, God has entrusted His power to the nature, and all the events occurred due to the co-creativity of God and nature. Secondly, God has no a direct influence on the external dimension, rather He is merely a Spirit of things who has influence on inner dimension.